2014
DOI: 10.1007/s40266-014-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Inappropriate Drug Therapy Prescription in the Elderly in Sweden from 2006 to 2013: Assessment Using National Indicators

Abstract: BackgroundMedication for elderly patients is often complex and problematic. Several criteria for classifying inappropriate prescribing exist. In 2010, the Swedish National Board of Health and Welfare published the document “Indicators of appropriate drug therapy in the elderly” as a guideline for improving prescribing for the elderly.ObjectiveThe aim of this study was to assess trends in the prescription of inappropriate drug therapy in the elderly in Sweden from 2006 to 2013 using national quality indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 31 publications
13
42
1
Order By: Relevance
“…In our study, 44 % of the study population used one or more potentially inappropriate medications in 2007 and 26 % in 2013, according to six of the quality indicators developed by the Swedish National Board of Health and Welfare [1]. This result agrees with the results of another study where six out of eight indicators showed an improvement according to the national quality indicators [15]. This study included the entire Swedish population aged 65 years or older, and four of the quality indicators were the same as in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 44 % of the study population used one or more potentially inappropriate medications in 2007 and 26 % in 2013, according to six of the quality indicators developed by the Swedish National Board of Health and Welfare [1]. This result agrees with the results of another study where six out of eight indicators showed an improvement according to the national quality indicators [15]. This study included the entire Swedish population aged 65 years or older, and four of the quality indicators were the same as in our study.…”
Section: Discussionsupporting
confidence: 89%
“…However, there is some evidence that the use of potentially inappropriate medication is decreasing among old people. In a newly published study, the extent of inappropriate drug use decreased between 2006 and 2013 in Sweden [15].…”
Section: Introductionmentioning
confidence: 99%
“…As such, a Swedish study found that the extent of inappropriate drug prescriptions for the aged (≥65 years of age) improved over the period 2006–2013 due to improved/safer prescribing practices adopted by physicians when dealing with elderly patients 46. Additionally, pharmacists play a major role in reducing suboptimal prescribing as disclosed in a review that evaluated the impact of pharmacists’ interventions to improve the appropriateness of prescribing in the aged 47.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults generally have a greater risk of medication‐related adverse events than younger individuals because they use more medications and because of age‐related physiological changes. Inappropriate prescribing of medication in elderly adults is common and can lead to higher healthcare costs, adverse drug reactions, hospitalization, and mortality . The economic burden of potentially inappropriate medication (PIM) use is substantial, estimated at $7.2 billion in 2001 .…”
mentioning
confidence: 99%